Exploring the focus of future CO2 emission reduction in China's industrial sectors. Issue 4 (17th April 2021) - Wu, Qunli; Gu, Shuting
Abstract: Marginal abatement cost (MAC) of CO2 plays a fundamental role in formulating industry environmental policies. In this paper, we measured the MACs of energy‐related CO2 among 40 industrial sectors during 2005–2017 based on parametric directional distance function, and there were significant differences between the results. Then, industrial sectors were classified into four categories, and we found 'low carbon intensity' type (type I, II) has higher MACs of CO2 than 'high carbon intensity' type (type III, IV); under the same level of carbon intensity, industrial sectors with lower CO2 emissions have higher MACs (type I>II, type III>IV). Moreover, capital intensity, technology progress, and ownership structure have positive effects on MACs, while energy intensity and energy consumption structure are negatively correlated with MACs. The research suggests: (1) The 'double control' of carbon intensity and CO2 emissions is necessary, however, reducing carbon intensity is still the primary target, and CO2 emission should also be controlled appropriately at the present stage. (2) Industrial sectors in type IV should be chosen as key industrial sectors to be supervised. (3) China should consider industry characteristics and implement "common but differentiated" emission reduction policies. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.